2017
DOI: 10.4269/ajtmh.16-0898
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Duration of Moderate-to-Severe Diarrhea among Children in Rural Western Kenya Enrolled in the Global Enteric Multicenter Study, 2008–2012

Abstract: Diarrheal disease is a leading cause of death among young children worldwide. As rates of acute diarrhea (AD; 1-6 days duration) have decreased, persistent diarrhea (PD; > 14 days duration) accounts for a greater proportion of the diarrheal disease burden. We describe factors associated with the duration of moderate-to-severe diarrhea in Kenyan children < 5 years old enrolled in the Global Enteric Multicenter Study. We found 587 (58%) children experienced AD, 360 (35%) had prolonged acute diarrhea (ProAD; 7-13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 45 publications
2
24
1
1
Order By: Relevance
“… 33 We did not distinguish between acute, persistent, or prolonged diarrhoea, yet evidence suggests that Cryptosporidium is associated with an extended duration of diarrhoea and that long-lasting diarrhoea could affect the long-term burden non-linearly. 34 Our findings call for further investigations about the prevalence of asymptomatic infection and how such infections can also lead to morbidity. Although our data suggest that Cryptosporidium infection in the absence of diarrhoea might impede linear growth, quantifying the prevalence of asymptomatic infection was beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 82%
“… 33 We did not distinguish between acute, persistent, or prolonged diarrhoea, yet evidence suggests that Cryptosporidium is associated with an extended duration of diarrhoea and that long-lasting diarrhoea could affect the long-term burden non-linearly. 34 Our findings call for further investigations about the prevalence of asymptomatic infection and how such infections can also lead to morbidity. Although our data suggest that Cryptosporidium infection in the absence of diarrhoea might impede linear growth, quantifying the prevalence of asymptomatic infection was beyond the scope of this work.…”
Section: Discussionmentioning
confidence: 82%
“…At enrollment caretakers were (1) asked how many days the case child had been experiencing diarrhea in the week before presenting at the health facility and (2) instructed on how to record the presence/absence of diarrhea for 14 days following enrollment on a Memory Aid form [ 18 ]. The total number of days of diarrhea was calculated as the sum of these durations, with a maximum of 21 possible diarrhea days, which may include multiple episodes [ 8 ]. Acute diarrhea was defined as having 1–6 days of diarrhea in the 21-day period; having 7–13 and ≥14 days refer to prolonged and persistent diarrhea , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Cryptosporidium has been associated with decreases in height-for-age z-scores in children, even in the absence of diarrhea symptoms [ 4 ]. Cryptosporidium infections have been associated with persistent diarrhea in Kenya [ 8 , 9 ]. Cryptosporidium is highly tolerant to disinfection with chlorine [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We attempted to conduct a phone follow‐up among cases to determine how many progressed to ProPD, but with limited success. A recent study in Kenya reported a higher follow‐up success rate and reported ProD and PD rates of 35% and 7% of the diarrhoea cases, respectively . We suggest that future diarrhoea studies should include follow‐up ; cell phone follow‐up warrants further exploration in particular, as it could be developed into a simple and cost‐effective tool to reach more children with ProPD.…”
Section: Discussionmentioning
confidence: 99%